2009
DOI: 10.2353/ajpath.2009.080596
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1 Expression Is Increased in Hepatocellular Carcinoma and Promotes Tumorigenesis

Abstract: Accelerated glycolysis is one of the biochemical characteristics of cancer cells. The glucose transporter isoform 1 (GLUT1) gene encodes a key rate-limiting factor in glucose transport into cancer cells. However, its expression level and functional significance in hepatocellular cancer (HCC) are still disputed. Therefore, we aimed to analyze the expression and function of the GLUT1 gene in cases of HCC. We found significantly higher GLUT1 mRNA expression levels in HCC tissues and cell lines compared with prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
224
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 303 publications
(232 citation statements)
references
References 36 publications
7
224
0
1
Order By: Relevance
“…S3). Although low glucose level could also induce a high level of GLUT-1, hypoxia would be the most possible cause of the increased GLUT-1 in our study due to the following reasons: GLUT-2, instead of GLUT-1, mediates glucose uptake in hepatocyte (14); therefore, a low glucose level in liver cancer cells may not trigger the overexpression of GLUT1; there is a documented strong association between hypoxia and liver tumor (15,16) that correlated the increased hypoxia with the observation of high level of the GLUT-1 in our study.…”
Section: Resultsmentioning
confidence: 74%
“…S3). Although low glucose level could also induce a high level of GLUT-1, hypoxia would be the most possible cause of the increased GLUT-1 in our study due to the following reasons: GLUT-2, instead of GLUT-1, mediates glucose uptake in hepatocyte (14); therefore, a low glucose level in liver cancer cells may not trigger the overexpression of GLUT1; there is a documented strong association between hypoxia and liver tumor (15,16) that correlated the increased hypoxia with the observation of high level of the GLUT-1 in our study.…”
Section: Resultsmentioning
confidence: 74%
“…However, one must be careful in interpreting the role of KLF5 in this setting because multiple factors are being up-regulated in tumor spheroids, as recently shown in a study using colon cancer cells (39). Interestingly, one such factor up-regulated in tumor spheroids is the HIF-1α target gene GLUT-1 (40). Nevertheless, consistent with our theory, we also found that increases in KLF5 were accompanied by a substantial up-regulation of survivin mRNA in spheroids (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To enable a high glycolytic capacity, the liver cancer tissue must attain an enhanced uptake of glucose. While glucose transporter 2 is most important in healthy liver, the fetal glucose transporter 1 is upregulated in HCC, and its expression is correlated with HCC proliferation and invasiveness [84][85][86][87]. Moreover, patients with a high glucose transporter 1 expression showed higher α-fetoprotein (HCC tumor marker) and poorer differentiation compared to the glucose transporter 1 low-expression cohort [88].…”
Section: Metabolic Alterations In Liver Cancermentioning
confidence: 99%